Prevalencia de brucelosis bovina (Brucella abortus) en Camales Municipales de la Provincia de Los Ríos - Aldaz Silva, Victor Manuel (2023)
Brucellosis has a worldwide distribution, this is one of the most important diseases in cattle and has different infection rates in all countries. The present work was carried out with the purpose of identifying the Prevalence of bovine brucellosis in Municipal Camales of the Province of Los Ríos, this research sampled the accredited municipal slaughter centers and those that are in the process of MABIO accreditation in the province of Los Ríos. (Quevedo, Ventana and Babahoyo. The population of interest were cattle destined for slaughter for marketing (n=450), having a total of males (n=144) and females (n=306). To know the health status destined for sacrifice and identify the possible reactors to proceed with the respective notification for the confiscation of the reproductive system and mammary glands. Bovine brucellosis has abortion as a clinical sign, hence the selection of this specific population. Blood was taken in the coccygeal vein, by this means obtaining the serum, to proceed with the diagnostic test that was carried out in the Phytopathology laboratory of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, 0.30 ul of (Rose Bengal) was used and 0.30 ul of serum on a glass plate to homogenize them, wait 4 minutes making circular movements, after which the diagnosis is read directly with a light. The result was that 100% of the cases were seronegative for Brucella Abortus.